2014
DOI: 10.1007/s10620-014-3248-6
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness and Diagnostic Effectiveness Analyses of Multiple Algorithms for the Diagnosis of Lynch Syndrome

Abstract: Background & Aims The optimal algorithm to identify Lynch syndrome (LS) among patients with colorectal cancer (CRC) is unclear. The definitive test for LS, germline testing, is too expensive to be applied in all cases. Initial screening with the Revised Bethesda Guidelines (RBG) cannot be applied in a considerable number of cases due to missing information. Methods We developed a model to evaluate the cost-effectiveness of 10 strategies for diagnosing LS. Three main issues are addressed: modeling estimates (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…http://dx.doi.org/10.1101/195537 doi: bioRxiv preprint first posted online Sep. 28, 2017; concluded that universal testing of CRC patients for LS based on sequencing alone will become more cost-effective than the two-step test when the cost of MMR gene sequencing drops to or below $609 USD, echoing a similar finding by Gould-Suarez et al [59,60] Based on our results, universal testing of pancreatic cancer patients using a panel test would identify pathogenic variants or MMR HiP-VUS in 1.4% of pancreatic cancer; this is quite comparable to currently accepted two-step universal testing of CRC patients, which identifies pathogenic MMR variants in about 1.2% of patients. [59] In a recent study, 11.8% of unselected patients with metastatic prostate cancer were found to carry pathogenic variants in DNA-repair genes.…”
Section: Discussionmentioning
confidence: 85%
“…http://dx.doi.org/10.1101/195537 doi: bioRxiv preprint first posted online Sep. 28, 2017; concluded that universal testing of CRC patients for LS based on sequencing alone will become more cost-effective than the two-step test when the cost of MMR gene sequencing drops to or below $609 USD, echoing a similar finding by Gould-Suarez et al [59,60] Based on our results, universal testing of pancreatic cancer patients using a panel test would identify pathogenic variants or MMR HiP-VUS in 1.4% of pancreatic cancer; this is quite comparable to currently accepted two-step universal testing of CRC patients, which identifies pathogenic MMR variants in about 1.2% of patients. [59] In a recent study, 11.8% of unselected patients with metastatic prostate cancer were found to carry pathogenic variants in DNA-repair genes.…”
Section: Discussionmentioning
confidence: 85%
“…A recent cost-effectiveness analysis estimated that if charges for germline testing dropped to $633–1518, universal germline testing of all newly diagnosed colorectal cancer cases would be more cost-effective than the various commonly used screening strategies. 64 …”
Section: The Evolving Nature Of Mismatch Repair Testing In Colorectalmentioning
confidence: 99%
“…In this issue of Digestive Diseases and Sciences, GouldSuarez et al [5] use decision analytic modeling to compare the cost-effectiveness of several strategies to diagnose LS among patients presenting with colorectal cancer. The strategies considered rely on first applying the revised Bethesda guidelines (RBG), or first testing colorectal cancers for features suggestive of LS [abnormal immunohistochemistry (IHC) or microsatellite instability (MSI)], or proceeding directly to germline testing for mutations in the DNA MMR genes.…”
mentioning
confidence: 99%
“…It is more difficult to judge how much we should we be willing to pay per incremental case of LS detected without knowing the downstream outcomes and costs. Figure 1 displays graphically the clinical (LS cases detected) and economic (total cost) outcomes for each strategy presented in Table 1 of the study by Gould-Suarez et al [5]. The slope connecting two points reflects the value of the ICER as the incremental cost per additional LS case detected by the more effective versus the less effective strategy.…”
mentioning
confidence: 99%
See 1 more Smart Citation